2006
DOI: 10.1029/2005jb003971
|View full text |Cite
|
Sign up to set email alerts
|

Millennial slip rate of the Longitudinal Valley fault from river terraces: Implications for convergence across the active suture of eastern Taiwan

Abstract: The Longitudinal Valley fault is a key element in the active tectonics of Taiwan. It is the principal structure accommodating convergence across one of the two active sutures of the Taiwan orogeny. To understand more precisely its role in the suturing process, we analyzed fluvial terraces along the Hsiukuluan River, which cuts across the Coastal Range in eastern Taiwan in the fault's hanging wall block. This allowed us to determine both its subsurface geometry and its long‐term slip rate. The uplift pattern of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 49 publications
5
83
0
Order By: Relevance
“…The seismicity of this fault also illuminated that it has a listric shape, dipping at 75° to a depth of 5.0 km, 60° between 5.0 -15.0 km deep, and finally 45° to a depth of 20.0 km. Several previous studies reported that the slip rate of this fault is between 20.5 -32 mm yr -1 (Chen 2006(Chen , 2010Shyu et al 2006bShyu et al , 2008. However, this fault is also known for its aseismic creeping (e.g., Angelier et al 1997;Lee et al 2001).…”
Section: Seismogenic Structures Of Taiwan and Their Parametersmentioning
confidence: 99%
“…The seismicity of this fault also illuminated that it has a listric shape, dipping at 75° to a depth of 5.0 km, 60° between 5.0 -15.0 km deep, and finally 45° to a depth of 20.0 km. Several previous studies reported that the slip rate of this fault is between 20.5 -32 mm yr -1 (Chen 2006(Chen , 2010Shyu et al 2006bShyu et al , 2008. However, this fault is also known for its aseismic creeping (e.g., Angelier et al 1997;Lee et al 2001).…”
Section: Seismogenic Structures Of Taiwan and Their Parametersmentioning
confidence: 99%
“…The 60°east-dipping LVF, which represents the main active structure of the LV, is characterized by high rates of oblique slip on its southern segment and by primary left-lateral strike-slip on its northern segment (Shyu et al 2005;Yu and Kuo 2001). The CRF, dipping 50°-60°westward underneath the eastern flank of the Central Range, is associated with the fast uplift of the Central Range (Shyu et al 2006). The Ruisui earthquake is believed to rupture a 30-35-km-long segment of this northeast-southwest trending CRF with a primary thrust mechanism, in agreement with the tectonic stress regime in this region.…”
Section: Introductionmentioning
confidence: 99%
“…The Luyeh Fault, which has been treated as a nearly pure thrust fault, runs along the west side of the Peinanshan massif (Lee et al 1998;Hu et al 2001). On the one hand, the Luyeh Fault seems to terminate gradually in the north (Shyu et al 2002) and was speculated to bend dramatically to E-W trending before joining the Lichi Fault in the south (Chen et al 2012). This is one of the main points we intend to address in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The river systems, which carry the sediments into the valley, often produce alluvial fans at the foot of the two ranges in the valley. In the study area of the southernmost Longitudinal Valley, along the Luyeh River there exist several (5 -7) levels of Holocene river terraces (Shyu et al 2002). The uppermost two terraces are the laterite gravels layers, which are widely distributed in the highlands of the Peinan tableland and the Kaotai tableland with a 14 C age of about 3500 yr (Shyu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation